Placebo‐controlled pilot trial testing dose titration and intravenous, intramuscular and subcutaneous routes for ketamine in depression. (30th March 2016) - Loo, C. K.; Gálvez, V.; O'Keefe, E.; Mitchell, P. B.; Hadzi‐Pavlovic, D.; Leyden, J.; Harper, S.; Somogyi, A. A.; Lai, R.; Weickert, C. S.; Glue, P.
Abstract : Objective: This pilot study assessed the feasibility, efficacy and safety of an individual dose‐titration approach, and of the intravenous (IV), intramuscular (IM) and subcutaneous (SC) routes for treating depression with ketamine. Method: Fifteen treatment‐refractory depressed participants received ketamine or midazolam (control treatment) in a multiple crossover, double‐blind study. Ketamine was administered by IV ( n = 4), IM ( n = 5) or SC ( n = 6) injection. Dose titration commenced at 0.1 mg/kg, increasing by 0.1 mg/kg up to 0.5 mg/kg, given in separate treatment sessions separated by ≥1 week, with one placebo control treatment randomly inserted. Mood, psychotomimetic and hemodynamic effects were assessed and plasma ketamine concentrations assayed. Results: Twelve participants achieved response and remission criteria, achieved at doses as low as 0.1 mg/kg. All three routes of administration resulted in comparable antidepressant effects. Fewest adverse effects were noted with the SC route. Antidepressant response, adverse effects and ketamine concentrations were dose‐related. Conclusion: Antidepressant response occurred at a range of doses and at <0.5 mg/kg. The dose‐titration approach is a practical method for optimizing the efficacy – side‐effects trade‐off on an individual patient basis. This pilot study provides preliminary evidence for SC injection as a practical, feasible and efficacious treatment approach.